Development of android-based learning media on tool sterilization materials - Fauziyah Harahap; Wilhelminari Br Saragih (Universitas Islam Negeri Sumatera Utara, 2023)
According to the analysis of student needs for sterilization material for tissue culture courses, it shows that learning media still has a limited role in the learning process. In terms of material and visualization, the learning media used cannot be explained in detail. Students still don't understand the material and really need Android-based learning media that is more flexible and well visualized. The purpose of this study was to find out the analysis of student needs, the design of instructional media, the level of feasibility of learning media from experts and the responses of lecturers and students as well as evaluations of students. The research method used is R&D, ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study were 96.70% of students needed Android-based learning media, media content designs namely: Instructions for Use, CP-MK, References, Materials, Videos, Exercises, Developer Profiles and EXIT. The feasibility level of the media is categorized as very feasible, the results of material experts are 100%, media experts are 96.5% and learning design experts are 94.5%. then the lecturer response was 83% and the student response was 92.52% included in the very decent category. then the evaluation stage obtained an n-gain score of 0.60 categorized as quite effective. The limitation of the research problem is that the material developed is limited to the topic of tool sterilization for tissue culture courses and the development used is limited to the evaluation stage, namely the media effectiveness testing stage.